The power of place: re-negotiating identity in hotel fiction - Pready, Joanna Elaine (2009)
The metropolitan hotel is a rich space for exploration in hotel fiction of the nineteenth and twentieth centuries due to its interesting connection with both the city and the home, and its positive and negative effects on the individual. Using spatial theory as a foundation for understanding how the hotel functions, and drawing on theorists such as Henri Lefebvre, Michel de Certeau, Edward D. Soja, Fredric Jameson, Yi-fu Tuan and David Harvey, this thesis offers an alternative approach to the culturally specific readings of past hotel studies; by contrast, it will draw on two alternate readings of the space: those which are concerned with the geographical and with the sociological make-up of the hotel. The ambition behind this thesis is to provide a framework for discussing novels from the realist tradition through to post-modern examples of spatial exploration.